What If the Ontological Basis of Consciousness are Quantum Exclusions? - Paciello, Arrigo (Journal of NeuroPhilosophy, 2025)
The aim of this paper is to advance a new hypothesis on the ontological correspondence between the quantum alternatives excluded from actualization in the quantum measurement (“collapse of the wave function”) and micro-phenomenal facts. Just as Heisenberg identified quantum potentia as a new type of ontological state distinct from the actualized state, it is a matter of conceiving a third type of ontological state, distinct from both the potential state and the actualized state. While Heisenberg's quantum potentia is distinguished as a superposition of potential space-time outcomes, the third type of ontological state, the quantum exclusion state, can be defined as a state of space-time outcomes annihilation. We can also conceive of quantum exclusions as Everettian branches that, deprived of physical quantities due to the collapse of the wave function, assume only phenomenal qualities. Quantum exclusions seem to be the only entities/states involved in the quantum measurement process, which are naturally supervenient but not logically supervenient on the actualized states (space-time events). Therefore, compared with Heisenbergian quantum potentiae, quantum exclusions might have fundamental advantages as the ontological basis of consciousness, as the “place of consciousness,” in terms of less vulnerability to Chalmers' conceivability arguments (e.g., zombie argument, inverted spectra argument), and most importantly because they do not exhibit the feature that makes quantum potentiae irreconcilable with our phenomenological evidence, namely superposition.